Pediatric Gastroesophageal Reflux Disease (GERD): A Literature Review - Farahdina Shahnaz; Yuda Satrio Wicaksono; Himawan Aulia Rahman (Archives of Pediatric Gastroenterology, Hepatology, and Nutrition, 2023)
Background: Gastroesophageal reflux disease (GERD) is a condition where stomach contents reflux into the esophagus, causing discomfort and complications. It is most prevalent in infants (26.9%) and lesser in children under 10 (3.2%) and over 10 years old (10.1%). Discussion: GERD is caused by frequent relaxations of the lower esophageal sphincter (LES), allowing stomach contents to escape into the esophagus. Symptoms vary with age, with infants experiencing regurgitation and irritability, while older children may have heartburn and nausea. Diagnosis requires differentiating GERD from similar conditions and may involve various tests, though their primary use lacks sufficient evidence. Nonpharmacological treatments include thickened feeding, reducing feeding volume but increasing frequency and possibly eliminating cow's milk protein. Pharmacological treatments include Proton Pump Inhibitors (PPIs), and Histamine Receptor Antagonists (H2RAs), though their efficacy varies. Prokinetics are generally not recommended due to lack of evidence. If all these treatments fail, anti-reflux surgery such as fundoplication can be considered. Conclusion: The hallmark of GERD is the presence of esophagitis during endoscopy. However, Barrett’s esophagus is rare in pediatric GERD patients. Factors indicating a worse prognosis include early onset age, an initial GERD diagnosis, and the need for PPI or combination of H2RA and PPI treatment.